2017
DOI: 10.4103/0253-7176.211757
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Anger with Alcohol use Treatment Outcome: Follow-up Study

Abstract: Background:Anger is seen as comorbid condition in psychiatric conditions. It has an impact on one's quality of life. It leads to variation in the treatment outcome. The present study is going to explore the relationship of anger with treatment outcome among alcohol users after 1 year of treatment. The data for the present study were taken from the project work on correlates of anger among alcohol users, funded by center for addiction medicine, NIMHANS, Bengaluru, Karnataka, India.Materials and Methods:A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…We have found that the majority of patients had high level of anger inferring that anger among individuals with alcohol use disorder is common. The study finding is supportive for the previous studies that high level of anger is observed among individuals with alcohol use disorder [7]. This could be explained in terms of the destructive effect of alcohol on cognition and emotions as it provokes maladaptive pattern of coping resulted in losing control over self and expression of anger [1].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We have found that the majority of patients had high level of anger inferring that anger among individuals with alcohol use disorder is common. The study finding is supportive for the previous studies that high level of anger is observed among individuals with alcohol use disorder [7]. This could be explained in terms of the destructive effect of alcohol on cognition and emotions as it provokes maladaptive pattern of coping resulted in losing control over self and expression of anger [1].…”
Section: Discussionsupporting
confidence: 88%
“…The connection also between aggression and alcohol use has also been reported [6]. Not merely during the course of detoxification, but alcohol has also interfered negatively with alcohol use treatment outcomes [7]. This shows the significant role of anger among individuals undergoing treatment of alcohol use disorder and their abilities to sustain their sobriety during and after the detoxification program [8].…”
Section: Introductonmentioning
confidence: 83%
See 2 more Smart Citations
“…3,[13][14][15][16] Although previous investigations have explored the association of anger with PSU, there are few studies that address aspects of trait anger between users and non-users of psychoactive substances. 17 The frequent and intense anger observed in users of psychoactive substances in clinical treatment has been considered a risk factor for relapse. [18][19][20][21][22] Within this context, the main objective of the present study is to understand, through a systematic review and meta-analysis, the relationship between anger scores in patients using psychoactive substances and non-user controls, including possible moderators such as age, sex, and withdrawal time.…”
Section: Introductionmentioning
confidence: 99%